2015
DOI: 10.1364/oe.23.005915
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of fs-laser induced sub-100-nm periodic surface structures on titanium

Abstract: In this work the formation of laser-induced periodic surface structures (LIPSS) on a titanium surface upon irradiation by linearly polarized femtosecond (fs) laser pulses with a repetition rate of 1 kHz in air environment was studied experimentally. In particular, the dependence of high-spatial-frequency-LIPSS (HSFL) characteristics on various laser parameters: fluence, pulse number, wavelength (800 nm and 400 nm), pulse duration (10 fs - 550 fs), and polarization was studied in detail. In comparison with low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 38 publications
10
72
0
3
Order By: Relevance
“…The pronounced ablation at scratches has been put in context of field enhancement as has been described recently. [34] In contrast to LIPSS formation at femtosecond laser ablation, [26,27] we find no ordered (or lamellar) surface structuring. The surface rather develops splash and finger structures, the latter having a micrometer diameter and thus efficiently modifying light reflection.…”
Section: Incubation On Silver and Gold Targets At Low Fluencementioning
confidence: 74%
See 3 more Smart Citations
“…The pronounced ablation at scratches has been put in context of field enhancement as has been described recently. [34] In contrast to LIPSS formation at femtosecond laser ablation, [26,27] we find no ordered (or lamellar) surface structuring. The surface rather develops splash and finger structures, the latter having a micrometer diameter and thus efficiently modifying light reflection.…”
Section: Incubation On Silver and Gold Targets At Low Fluencementioning
confidence: 74%
“…In particular, we find that corrugation here is on a micrometer scale, comparable to the laser wavelength. It is self‐organized in size and morphology by the laser‐surface interaction reminding of structure formation, for femtosecond laser pulses. Figure shows scanning electron microscope images of a Au target surface after a different number of applied shots of 1 mJ pulse energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For metals like Ti, Al, and Au, it was shown that nanoscale surface boiling plays a role in sub-threshold damage, as well as above-threshold spallation by femtosecond laser pulses [39,40]. Although thermal material modification and rearrangement were detected at different time scales compared to the exciting light pulses, the ripple formation is significantly influenced by plasmons initially induced by the ultrafast laser pulses [39].…”
Section: Introductionmentioning
confidence: 99%